Student Worksheet Development on the Math Division Material Based on the PMRI Approach for Fifth-Grade Elementary School Students - Arief Kuswidyanarko; Miftahul Jannah; Rohana Rohana (Universitas Pendidikan Ganesha, 2021)
Students have difficulty learning mathematics, so it can be concluded that mathematics is complicated, especially for elementary school students. It has an impact on student learning outcomes that decline. This study aims to produce LKPD on material distribution based on a valid and practical PMRI approach for learning. The development research used is research and development (R&D) using a 4D model developed by Thiagarajan consisting of four stages: define stage, design stage, development stage, and dissemination stage. Data was collected through interviews, questionnaires, and observations. The instrument used to collect data is a questionnaire. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The results obtained from the validation test by experts with an average rating of 87.5% are excellent categories. The student responses in the limited trial obtained an average percentage of 84.58% in the efficient category, and the student responses in the field trial with 82.40% in the efficient category. The results of the assessment of the educator's response were 88.75% in the efficient category. Based on these data, the LKPD in the distribution material based on the PMRI approach has met the criteria for validity and practicality so that the LKPD developed is feasible to be used in the learning process.